Implementasi Kebijakan Pengelolaan dan Pelayanan Informasi Publik di KPU Kota Bengkulu - Yoga Agriyansyah; Rekho Adriadi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
The management and service of public information at the Bengkulu City KPU is based on the KPU regulations which serve as guidelines for the Bengkulu City KPU in carrying out a program of activities. Through the writing of this thesis, the problem raised is how to implement public information management and service policies at the Bengkulu City KPU and what factors are the obstacles and supporters in the implementation of public information management and services at the Bengkulu City KPU. The purpose of this study is to find out and understand how the implementation of public information management and service policies at the Bengkulu City KPU and to find out what are the inhibiting and supporting factors in the implementation of public information management and service policies at the Bengkulu City KPU. This study uses a qualitative method which ultimately produces descriptive data in the form of written or spoken words from people and observed behavior. Data collection techniques used in this thesis are observation, interviews and documentation. This study uses the theory of policy implementation from Charles O Jones. The results of this study reveal that the implementation of public information management and service policies at the Bengkulu City KPU is quite good, because the services provided have met the requirements written in PKPU No. 1 of 2015 concerning the management and service of public information.